2020
DOI: 10.1093/mnras/staa1685
|View full text |Cite
|
Sign up to set email alerts
|

Counterparts of Far Eastern Guest Stars: Novae, supernovae, or something else?

Abstract: Historical observations of transients are crucial for studies of their long-term evolution. This paper forms part of a series of papers in which we develop methods for the analysis of ancient data of transient events and their usability in modern science. Prior research on this subject by other authors has focused on looking for historical supernovae and our earlier work focused on cataclysmic binaries as classical novae. In this study we consider planetary nebulae, symbiotic stars, supernova remnants, and pul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 70 publications
1
7
0
Order By: Relevance
“…This is presented here. In Section 2, we discuss the first two papers on previous historical SNe and novae (Hoffmann 2019; Vogt et al 2019), in Section 3 additional papers on their nova suggestions (Hoffmann et al 2020;Hoffmann & Vogt 2020a, 2020b, and in Section 4 we finish with a summary and final remarks. 1 Neuhäuser et al (2021a) have shown in detail that the sources used for two of the highlights in Hoffmann and Vogt (2020b), namely a presumable new historical SN AD 1 The papers by Vogt et al (2019), ), Hoffmann et al (2020, and Vogt (2020a, 2020b) were submitted without the consent of RN and after the participation of SH in the project had been terminated in a mutual agreement between RN and SH in February 2019.…”
Section: Introduction: Historical Novae and Supernovaementioning
confidence: 99%
See 4 more Smart Citations
“…This is presented here. In Section 2, we discuss the first two papers on previous historical SNe and novae (Hoffmann 2019; Vogt et al 2019), in Section 3 additional papers on their nova suggestions (Hoffmann et al 2020;Hoffmann & Vogt 2020a, 2020b, and in Section 4 we finish with a summary and final remarks. 1 Neuhäuser et al (2021a) have shown in detail that the sources used for two of the highlights in Hoffmann and Vogt (2020b), namely a presumable new historical SN AD 1 The papers by Vogt et al (2019), ), Hoffmann et al (2020, and Vogt (2020a, 2020b) were submitted without the consent of RN and after the participation of SH in the project had been terminated in a mutual agreement between RN and SH in February 2019.…”
Section: Introduction: Historical Novae and Supernovaementioning
confidence: 99%
“…Neuhäuser et al 2021b). In this article, we deal with suggested historical novae and SNe (Hoffmann et al 2020; Hoffmann & Vogt 2020a, 2020b)—however, many of their candidates are not star‐like, but obviously comets.…”
Section: Introduction: Historical Novae and Supernovaementioning
confidence: 99%
See 3 more Smart Citations